Middlebrow Modernism Britten's Operas and the Great Divide - Chowrimootoo, Christopher (University of California Press, 2018)
Situated at the intersection between the history, historiography and aesthetics of twentieth-century music, this study uses Benjamin Britten's operas to illustrate the ways in which composers, critics and audiences mediated the "great divide" between modernism and mass culture. Reviving mid-century discussions of the "middlebrow," Chowrimootoo demonstrates how these works allowed audiences to have their modernist cake and eat it: to revel in the pleasures of consonance, lyricism and theatrical spectacle, even while enjoying the prestige that came from rejecting them. By focusing on moments when reigning aesthetic oppositions and hierarchies threatened to collapse, Middlebrow Modernism offers a powerful model for recovering shades of grey in the black-and-white historiographies of twentieth-century music.